Clinical Features Of Liver Rupture Related To Severe Preeclampsia At The National Maternal Perinatal Institute - Meza-Salcedo, Ronald (2019)
The liver rupture in pregnancy (LRP) is a disease of low incidence but high morbidity and mortality, being a devastating complication in patients with severe preeclampsia (SPE), approximately 200 cases in the world literature and some individual cases in the national literature are reported. Objectives: The main objective was to describe the most frequent clinical features in patients with SPE admitted to the Unidad de Cuidados Intensivos Materna (UCIM) at the Instituto Nacional Materno Perinatal (INMP). Materials and methods: The medical records of patients with the diagnosis of LRP treated in the UCIM in the period between 2004 and 2013 were reviewed, a record of data collection was used and frequency analysis was performed for most common signs and symptoms.